An Urartian stele base from Beydamarı, Turkey - Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
This article describes an Urartian stele base discovered in 2010 in eastern Turkey, during an epigraphical survey directed by Prof. Mirjo Salvini around Lake Van as part of the activities of CNR – ICEVO. During work in the region between 20 July and 9 August, 2010, several new archaeological sites and inscriptions were discovered, including the Urartian stele base discussed below. On 7 August 2007 an Urartian stele was discovered in the village of Bulutpınar, 25 km north-west of Patnos in Ağrı province, at the north foot of Bulutpınar Dağı (2024 m) (Figure 1). The basalt stele bears an inscription of Argišti II (713-? BC), one of the few inscriptions currently known for this Urartian king (Figure 2). The content of the inscription was published by Mirjo Salvini shortly afterwards, first in 2008 in the ‘Corpus of Urartian Text’ and later republished in 2010 with further remarks on the content of the text.